Asuhan Kebidanan Komprehensif pada Ny. S di RSIA Masyita Makassar - Shaqila Ainurcynthia; Halida Thamrin; Azrida M (Window of Midwifery Journal, 2025)
Comprehensive care and Continuity of Care is a comprehensive approach in midwifery services that includes pregnancy, childbirth, postpartum period, newborn care, and family planning counseling. The goal is to provide integrated and adequate health services to reduce maternal mortality and improve the health of mothers and babies. This study aims to implement comprehensive midwifery care for Mrs. "S" at Masyita Makassar Maternity Hospital. The care provided covers all stages, namely pregnancy, childbirth, newborn care, postpartum period, and family planning counseling. The care process is carried out using the 7-step midwifery management approach according to Varney, and recorded using the SOAP format. Data were collected through interviews, observations, physical examinations, and document reviews. The results of the care showed that Mrs. S G1P0A0, 38 weeks and 5 days of gestation, underwent 6 antenatal visits with examination results within normal limits without any signs of pregnancy danger. During labor, the baby was born spontaneously and immediately cried. The baby is a girl with a weight of 3,240 grams, a body length of 49 cm, a head circumference of 34 cm, and a chest circumference of 34 cm. Two postpartum visits were conducted, and no complications were found. Family Planning Counseling for the mother had not planned to use contraception. From this care, it is hoped that the patient will increase her knowledge and awareness of possible complications, as well as become a meaningful experience for the author and improve her skills in providing comprehensive midwifery care.